Enhanced Optical and Electrical Properties of IGZO/Ag/IGZO for Solar Cell Application via Post-Rapid Thermal Annealing - Chanmin Hwang; Taegi Kim; Yuseong Jang; Doowon Lee; Hee-Dong Kim (Nanomaterials)
In this paper, we optimized IGZO/Ag/IGZO (IAI) multilayer films by post-rapid thermal annealing (RTA) to enhance the electrical conductivity and optical transmittance in visible wavelengths for solar cell applications. Our optimized device showed an average transmittance of 85% in the visible range, with a lowest sheet resistance of 6.03 Ω/□ when annealed at 500 °C for 60 s. Based on these results, we assessed our device with photo-generated short circuit current density (JSC) using a solar cell simulator to confirm its applicability in the solar cell. IAI multilayer RTA at 500 °C for 60 s showed a highest JSC of 40.73 mA/cm2. These results show that our proposed IAI multilayer film, which showed a high optical transparency and electrical conductivity optimized with post RTA, seems to be excellent transparent electrode for solar cell applications.